Near room-temperature formation of Cu3Sn: In-situ synchrotron X-ray diffraction characterization and thermodynamic assessments of its nucleation. (July 2021) - Song, T.; Schmid-Fetzer, R.; Yan, M.; Qian, M.
Abstract: The fabrication of Cu3 Sn at near room temperatures and atmospheric pressure remains out of reach. We propose a novel concept to address this challenge by exploiting both the classical nano-island model for dealloying and the nanocurvature effect on nucleation, in conjunction with bespoke precursor alloy design. In-situ synchrotron X-ray diffraction (XRD) confirmed significant formation of Cu3 Sn at both 70°C and 55°C in 180 min via a dealloying-realloying process in the designed precursor alloy Al67Cu18Sn15, compared with much slower formation at 125°C by conventional approaches. Furthermore, Cu3 Sn formed just 10 min after Cu6 Sn5 emerged at 70°C, being two orders of magnitude faster than in Cu/Cu6 Sn5 diffusion couples at 125°C. The energy barrier to the formation of a lenticular Cu3 Sn nucleus on Cu6 Sn5 nanocaps was assessed systematically using the CALPHAD approach through the initial driving force ( DF ) concept and DF -plateau method. The predictions were benchmarked against diffusion couple studies, which fully supported the experimental results. In addition, the in-situ synchrotron XRD data on phase evolution was analysed in detail using the well-established Johnson-Mehl-Avrami-Kolmogorov (JMAK) model, which provided further fundamental support to our conceptual design. The concept and methodology demonstrated are expected to be applicable to the fabrication of other challenging materials. Graphical abstract: Image, graphical abstract